2019
DOI: 10.1017/thg.2019.102
|View full text |Cite
|
Sign up to set email alerts
|

The Florida State Twin Registry

Abstract: The Florida State Twin Registry has existed for nearly two decades, and it grew primarily over 10 years as part of the Florida Learning Disability Research Center at Florida State University. The registry contains 2753 sets of twins and other multiples in Florida. The mean age of the sample currently is 17.96 years (SD = 2.05). The registry is diverse in terms of race and ethnicity (49% White, 19% African American, 24% Hispanic and 8% mixed or other). The characteristics of the samples and measures in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…As such, we examined the relation between both grit and mindset on current, future, and change in reading comprehension ability in a twin sample. We used data from 422 twin pairs (171 monozygotic pairs, 251 dizygotic pairs) drawn from the Florida Twin Project on Reading, Behavior and Environment (Taylor et al, 2019). The racial composition of the sample included 1.…”
mentioning
confidence: 99%
“…As such, we examined the relation between both grit and mindset on current, future, and change in reading comprehension ability in a twin sample. We used data from 422 twin pairs (171 monozygotic pairs, 251 dizygotic pairs) drawn from the Florida Twin Project on Reading, Behavior and Environment (Taylor et al, 2019). The racial composition of the sample included 1.…”
mentioning
confidence: 99%
“…This study utilized a subsample of school-age children who participated in the Florida Twin Project on Reading, Behavior, and Environment, a large study of twins attending schools throughout Florida ( Taylor et al, 2019 ). Participants were selected from the larger study based on their caregivers' report of their race/ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…During the 2012–2013 school year, questionnaires and testing packets were mailed to the homes of participants enrolled in the larger project ( Taylor et al, 2019 ). Parents completed self-report measures concerning their children's race and family socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, what is not accounted for by genetic influences is accounted for by environmental influences. It is especially the case that twin samples with greater socioeconomic and racial diversity show higher estimates of environmental influences than more homogenous samples (see Little et al, 2017), such as our Florida Twin Project on Reading (Taylor et al, 2019). Further evidence from the behavioral genetic literature on individual differences in school DEVELOPMENTAL BEHAVIORAL GENETICS 4 achievement indicates that these genetic and environmental influences should not be considered separately from each other (e.g., Purcell, 2002).…”
mentioning
confidence: 99%
“…Proving that point, a metaanalysis we published on the genetic and environmental influences on reading comprehension, which summarized all available published and unpublished developmental behavioral genetics studies, found only 7 of 37 studies included a sample that was not at least 75% White (Little et al, 2017). To make that number worse, these 7 studies were publications from only two samples of all possible twin samples around the world, the National Longitudinal Survey of Youth DEVELOPMENTAL BEHAVIORAL GENETICS 9 (NLSY) sample (Rodgers et al, 1994) and the Florida Twin Project on Reading (Taylor et al, 2019). Beyond reading comprehension, Tucker-Drob and Bates (2016) mention one other study, Tucker-Drob et al (2011), that was nationally representative of the U.S. and therefore the sample was not overwhelmingly White (this sample did not include reading which is why it was not captured by Little et al, 2017).…”
mentioning
confidence: 99%